A LIVRE INICIATIVA E O PRINCÍPIO DA FUNÇÃO SOCIAL NAS ATIVIDADES EMPRESARIAIS NO CONTEXTO GLOBALIZADO - Sacchelli, Roseana Cilião (Revista da AJURIS, 2013)
FREEDOM INITIATIVE AND THE PRINCIPLE OF SOCIAL FUNCTION IN BUSINESS ACTIVITIES IN THE CONTEXT GLOBALIZED RESUMO: A ordem jurídica instituída com a Constituição Federal de 1988 estabeleceu o princípio da função social como alicerce do exercício das atividades econômicas das empresas. O modelo econômico introduzido no art. 170 consagra o princípio da livre iniciativa como fundamento da construção da ordem econômica, entretanto, o mesmo artigo limita a atuação empresarial ao incumbir a realização obrigatória dos objetivos sociais. A proposta da investigação é analisar as implicações decorrentes da incidência do princípio da função social sobre as atividades empresariais no desempenho do papel primordial de gerar riqueza, na produção e circulação de bens e serviços, no Estado Democrático de Direito. São observadas as condições desfavoráveis na atuação das empresas nacionais em competir com outras provenientes de economias protecionistas ou descomprometidas com os ditames da justiça social. Reflete-se sobre políticas de estímulos para promover o fortalecimento e sustentabilidade das empresas, no atual ambiente globalizado, essenciais para concretizar os objetivos fundamentais da construção da sociedade mais justa com desenvolvimento econômico. PALAVRAS-CHAVE: Livre iniciativa; função social; atividades empresariais; globalização. ABSTRACT: The legal order established with the 1988 Federal Constitution established the principle of social function as a foundation for the exercise of economic activities of enterprises. The economic model introduced in art. 170 enshrines the principle of free enterprise as the foundation of building the economic order, however, that Article limits the business activity to instruct the implementation of mandatory social goals. The proposed research is to analyze the implications of the impact of the principle of social function on the performance of business activities in the primary role of generating wealth, production and circulation of goods and services in the democratic state of law. Unfavorable conditions are observed in the performance of national firms to compete with other economies from protectionist or uncommitted to the dictates of social justice. Reflects on politics of incentives to promote the consolidate and sustainability of businesses, in actual globalized environment, they are so essential to achieve the fundamental goals of building more just society with economic development. KEYWORDS: Free enterprise; social function; business activities; globalization. SUMÁRIO: Introdução; 1 Do Estado Liberal ao Estado Democrático de Direito;2 A livre iniciativa na ordem econômica; 3 Desenvolvimento econômico;4 A livre iniciativa e o desenvolvimento econômico;5 A livre iniciativa e as atividades empresariais; 6 Limitações à liberdade de iniciativa;7 A incidência da função social nas atividades empresariais;8 A globalização e as atividades empresariais; 9 Fortalecimento e sustentabilidade das empresas; Conclusão; Referências. SUMMARY: Introduction; 1 State of the liberal democratic state; 2 The free enterprise in economic order; 3 The economic development; 4 The free enterprise and economic development; 5 The free enterprise and business activities; 6 Limitations to freedom initiative; 7 The impact of social function in corporate activities; 8 Globalization and business activities; 9 Strengthening and sustainability of business; Conclusion; References.